Efficacy of using plant ingredients as partial substitute of fishmeal in formulated diet for a commercially cultured fish, Labeo rohita - Sumaiya Akter; Md. Ayenuddin Haque; Md. Al-Amin Sarker; Usman Atique; Sonia Iqbal; Pallab Kumer Sarker; Bilal Ahamad Paray; Takaomi Arai; M. Belal Hossain (Frontiers in Sustainable Food Systems)
Reliance on fish meal can be reduced by incorporating plant-based ingredients, making aquaculture more economical, sustainable and environmental friendly. In this study, the efficacy of plant protein ingredients (PPI) such as mustard oil cake (MOC), soybean meal (SBM) and rice bran (RB) as Partial substitute of fishmeal (FM) was investigated for a commercially important fish, Labeo rohita in cages for 90 days. Three experimental diets, labeled as Diet 1, Diet 2, and Diet 3, were formulated to be isonitrogenous (with protein content ranging from 32.20 to 32.29%) and iso-caloric (with gross energy ranging from 4.12 to 4.17 kcal/g). These diets contained different proportions of PPI (45, 68, and 79%) and FM (46, 23, and 11%, respectively). Square-shaped cages with a volume of 1m3 (1 m × 1 m × 1 m) were stocked with 40 fish/m3 each with an average initial weight of 52.97 g in triplicates. Fish were hand-fed to apparent satiation twice daily for 7 days a week at a feeding rate of 5% in the initial month and 3% for the rest of the culture period. 50% of the caged fish was sampled monthly to monitor growth performance and at the termination of the experiment, all the fish was harvested to measure production economics performance. The results indicated improved growth performance and higher feed utilization at Diet 2, yielding significantly (p < 0.05) higher fish production compared to Diet 3, while these parameters were insignificant with Diet 1. By replacing FM with PPI, the total feed cost compared to Diet 1 was reduced to 20.62 and 32.76% for Diet 2 and Diet 3, respectively. The replacement of 50% FM in Diet 2 also yielded a 15.61% higher total economic net return than the Diet 1 group. However, a higher inclusion rate of PPI in Diet 3 potentially reduced fish growth, with a consequent decline of 41.61% total economic net return compared to the Diet 1 group. In conclusion, the replacement of 50% FM in Diet 2 compared to Diet 1 returned a higher benefit–cost ratio (1.72) among the feeding groups. Therefore, this FM replacement experiment suggested a 50% FM replaced diet as an unconventional, cost-effective, and readily available novel protein source without compromising the inherent nutritional quality of fish and feed in the cage culture of L. rohita. The results could be widely applicable to the fast-growing approach of cage culture technology across Asia and beyond.